2010
DOI: 10.1200/jco.2009.25.3575
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of KW-0761, a Defucosylated Humanized Anti-CCR4 Antibody, in Relapsed Patients With Adult T-Cell Leukemia-Lymphoma and Peripheral T-Cell Lymphoma

Abstract: KW-0761 was tolerated at all the dose levels tested, demonstrating potential efficacy against relapsed CCR4-positive ATL or PTCL. Subsequent phase II studies at the 1.0 mg/kg dose are thus warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
274
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 323 publications
(287 citation statements)
references
References 40 publications
10
274
1
2
Order By: Relevance
“…We have shown that a therapeutic anti-CCR4 mAb does deplete Treg cells in vitro (39,40) and in vivo in humanized mice (27). Furthermore, we confirmed the CD25 + CD4 + FOXP3 + Treg depletion activity mediated by the humanized anti-CCR4 mAb mogamulizumab (KW-0761) in humans (41)(42)(43)(44). Therefore, a combination of Tax-CTL adoptive immunotherapy with mogamulizumab to act not only as an anti-ATL agent but also to deplete Treg cells would be promising.…”
Section: Discussionsupporting
confidence: 55%
“…We have shown that a therapeutic anti-CCR4 mAb does deplete Treg cells in vitro (39,40) and in vivo in humanized mice (27). Furthermore, we confirmed the CD25 + CD4 + FOXP3 + Treg depletion activity mediated by the humanized anti-CCR4 mAb mogamulizumab (KW-0761) in humans (41)(42)(43)(44). Therefore, a combination of Tax-CTL adoptive immunotherapy with mogamulizumab to act not only as an anti-ATL agent but also to deplete Treg cells would be promising.…”
Section: Discussionsupporting
confidence: 55%
“…A meta-analysis suggested that AZT therapy in combination with IFN may possess value, although morbidity and a lack of efficacy in patients with prior chemotherapy remain (29,30). Antibody-based approaches including use of daclizumab, alemtuzumab, and anti-CCR4 showed value but are not curative (31)(32)(33)(34). Allogeneic bone marrow transplantation is an aggressive approach that is curative in select patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose, subcutaneous alemtuzumab appears to be safe and efficacious in selected patients with advanced-stage MF/SS provided with appropriate supportive care. Monoclonal antibodies targeting additional T-cell specific antigens, including CD2 [326], CD4 [327], CD25 [328], and CCR4 [329][330][331] are being explored and appear promising.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%